Can We Help Care Providers Communicate More Effectively With Persons Having Dementia Living in Long-Term Care Homes?. (February 2017) - McGilton, Katherine S.; Rochon, Elizabeth; Sidani, Souraya; Shaw, Alexander; Ben-David, Boaz M.; Saragosa, Marianne; Boscart, Veronique M.; Wilson, Rozanne; Galimidi-Epstein, Karmit K.; Pichora-Fuller, M. Kathleen
Background: Effective communication between residents with dementia and care providers in long-term care homes (LTCHs) is essential to resident-centered care. Purpose: To determine the effects of a communication intervention on residents' quality of life (QOL) and care, as well as care providers' perceived knowledge, mood, and burden. Method: The intervention included (1) individualized communication plans, (2) a dementia care workshop, and (3) a care provider support system. Pre- and postintervention scores were compared to evaluate the effects of the intervention. A total of 12 residents and 20 care providers in an LTCH participated in the feasibility study. Results: The rate of care providers' adherence to the communication plans was 91%. Postintervention, residents experienced a significant increase in overall QOL. Care providers had significant improvement in mood and perceived reduced burden. Conclusion: The results suggest that the communication intervention demonstrates preliminary evidence of positive effects on residents' QOL and care providers' mood and burden.